On the effect of fluid temperature in hydrodynamic cavitation on a chip reactors - Seyedreza Tebyani; Farzad Rokhsar Talabazar; Morteza Ghorbani; Ali Koşar (International Journal of Thermofluids)
This study presents an experimental investigation on the effects of the fluid temperature on hydrodynamic cavitation (HC) inside microfluidic devices (HC reactors) with multiple parallel microchannels. Three different reactors featuring microchannel configurations with hydraulic diameters of 89, 66, and 48 micrometers including 9, 21, and 37 microchannels respectively, were fabricated using the semiconductor-based microfabrication techniques. The microchannels have side wall roughness elements with a length of one-third of the entire microchannel length and a height of one-tenth of the hydraulic diameter. The fabricated HC reactors enable the investigation of cavitating flows under different thermophysical conditions at operating pressures ranging from 1.7 to 4.1 MPa and fluid temperatures at 23 °C, 33 °C, and 43 °C, and allow the observation of different cavitating flow morphologies, e.g., sheet, shear, and cloud cavities. According to the results, an increase in the temperature by 10 °C significantly raised the cavitation intensity. Furthermore, the scale effects amplify the effect of the temperature changes. Accordingly, the effect of the temperature is more dominant on the microscale compared to macroscale. An increase in the fluid temperature from 23 °C to 33 °C can double the cavitation penetration length in some microchannels within Reactor 1 at an upstream pressure of 3 MPa. The average penetration length at the extension region also increases (by approximately 70 % for Reactor 1, 50 % for Reactor 2, and 35 % for Reactor 3) upon change in the fluid temperature. The change in the cavitation intensity was larger for the temperature increase from 23 °C to 33 °C than for the increase from 33 °C to 43 °C which emphasizes the increasing dominance of thermal effects with temperature. This study offers understanding how a change in thermal properties influences HC at the microscale. The findings of this study can be utilized for scaling efforts in various applications relying on cavitation such as water treatment, microreactors, nanomaterial synthesis, and micro mixing.